PENGARUH LATIHAN FISIK TERHADAP TINGKAT DEPRESI LANJUT USIA : LITERATURE REVIEW - Paramudita Apriliyani Cha Ayu Pitaloka, - (2020)
Various the problem that happen on Step elderly salah only one is elderly that exposed to depression, power healthyn must able to To do way for bring down level depression elderly is wrong only one with To do practice physical. As for aim research this is for knowing influence practice physical elderly to level depression elderly Method that used is study literature from the results search through data base that can accessed through Google Schoolar and Pubmed. Literature criteria used with keywords "The Effect of Physical Exercise To Depression Elderly ". Or " Effects of physical exercise on elderly depression "Based on hasil search had been was found 6 article. Then, author looking for difference, similarity, give out opinion and idea idea the latest then summarize literature the. Based on 6 research that is obtained that practice physical able to handle problem depression on elderly Ada difference the results before and after To do practice physical. Could be concluded that with To do practice physical 15-20 minute / day During 4 month, too gymnastics yoga and elderly During 8 Sunday. And is obtained the results from 6 research that had been done sbefore that elderly rarely relapse disease his depression and able to socialize back with person lain, due to rutin To do latihan physical. Author recommend a elderly for apply practice physical for handle problem depression in the elderly. Keywords: Depression, Elderly, Physical Exercise